Transition-metal-catalyzed intramolecular cyclization of amido(hetero)arylboronic acid aldehydes to isoquinolinones and derivatives - Burke, Anthony (2016)
We report an innovative and simple three step high yielding synthesis of a library of 14 chiral isoquinolinone and azepinone derivatives with benzyl, pyridyl and thiophene cores starting from amidoarylboronic acid aldehydes. These products have potential for treating neuro-degenerative diseases. The key reaction in this synthetic pathway was an efficient metal-catalyzed (with Rh, Cu and Pd catalysts) intramolecular cyclization. A maximum yield of 87% was obtained using a Rh(I) catalyst.